STRUCTURAL ANALYSIS OF UNPUBLISHED CHAGATAI-PERSIAN DICTIONARIES OF THE 16th–18th CENTURIES: LEXICOGRAPHIC AND SOCIOCULTURAL ASPECTS - Galiya Kambarbekova; Kuanyshbek Kari (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
The investigation delves into Chagatai-Persian dictionaries from the 16th to the 18th centuries, preserved in the Central Library of Punjab University. The article aims to study the structural features of these dictionaries in the context of their sociocultural significance and influence on the further development of Turkic languages. These invaluable medieval artifacts underwent detailed scrutiny using multiple methods, encompassing structural, lexical, codicological, lexicographic and sociocultural analyses. Within a single manuscript cover, there exist six treatises on the Turkic-Persian lexicon alongside a textbook elucidating Turkic language grammar. These are inscribed in the Perso-Arabic script, a writing system employed for the Chagatai language. The chief lexicographic design integrates headwords and their explanations in couplets, avoiding any typographic or grammatical demarcation. The artful use of rhyme schemes is evident in the systematic arrangement of headwords. A thorough scrutiny of these medieval Chagatai-Persian dictionaries brings to light their distinct lexicographical framework, crafted meticulously to support linguistic conservation. These works capture a wide spectrum of vocabulary from different Turkic territories, underlining the endeavor to encapsulate a broad cultural legacy. Elements such as rhyming masnavi-inspired explanatory sentences, thematic clusters, and dedicated segments on commands and equine terminology are observed. Notably, the integration of Persian elements, especially in the form of auxiliary verbs, symbolizes a fusion of languages. The dictionaries showcase an emphasis on practical vocabulary acquisition through the harmonious pairing of headwords with poetic contexts, devoid of typographic or grammatical deviations. Despite the headword’s seamless integration, there is meticulous attention to maintaining rhyming continuity. The rarity of prefaces is counterbalanced by the richness of colophons, which offer vital details about the manuscript. Though the Chagatai language receded over time, the indelible mark left by these dictionaries endures, with remnants identifiable in modern Turkic vocabularies. A more exhaustive comparative exploration of these works could further deepen insights into Chagatai linguistics and lexicographic practices during the medieval period. This study also triggers broader reflections on the pivotal role of bilingual lexicons in safeguarding vulnerable linguistic treasures. By methodically presenting and analyzing these linguistic gems, the investigation facilitates their appreciation within scholarly circles, underscoring the Turkic cultural legacy. This also solidifies their recognition as prime examples of the mutual literary interplay between Turkic and Persian traditions, a relationship rooted in the medieval timeframe.